Sarana Digital dan Nondigital Dalam Metode Pengembangan Ide Pada Proses Desain Produk - Wibisana, Intan Prameswari; Sari, Nedina; Syarief, Achmad (Fakultas Seni Rupa dan Desain ITB, 2025)
Rapid development of digital technology has had enormous impact on the design process, including in designing functional products. This study investigates the use of digital and non-digital methods and tools in the functional product design process, especially at the idea development stage. This investigation carried out by distributing online questionnaires to product design practitioners as respondents. In this questionnaire, respondents were asked to answer questions related to their idea development process. New insights found in this research are the use of digital (computers, tablets, smartphones, etc.) and non-digital (pencils and paper, wood, metal, clay, etc.) tools that are used simultaneously. Therefore, non-digital tools are not abandoned by the respondents and remain an important part of the functional product design process. The implication is that despite the rapid development of digital tools, the skill to use both digital and non-digital is equally important for a product designer, and as part of design education.